Effect of extender oils on the stress relaxation behavior of thermoplastic vulcanizates (eXPRESS Polymer Letters)
The long term mechanical behavior of oil extended thermoplastic vulcanizates (TPV) based on polypropylene (PP) and acrylonitrile-butadiene rubber (NBR) has been characterized by means of stress relaxation experiments. The morphology of TPV and the phase specific oil distribution which depend on the content and type of oil as well as on the mixing regime have been characterized by means of Atomic Force Microscopy (AFM), Dynamic Mechanical Thermal Analysis (DMTA) and Differential Scanning Calorimetrie (DSC). The discussion of the stress relaxation behavior was carried out using the two-component model, which allows splitting the initial stress into two components: a thermal activated stress component and an athermal one. A master curve was created by shifting the relaxation curves vertically and horizontally towards the reference curve. The vertical shift factor bT is a function of the temperature dependence of the athermal stress components. It was found that the oil distribution strongly affects the athermal stress component which is related to the contribution of the structural changes, e.g. crystallinity of the PP phase and the average molecular weight between the crosslinks of the NBR phase. From the temperature dependence of the horizontal shift factor aT the main viscoelastic relaxation process was determined as the α-relaxation process of the crystalline PP phase. It is not dependent on the polarity and content of the oil as well as the mixing regime.